2021
DOI: 10.1029/2020jb021356
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Attenuation and S‐Velocity Structures in Beneath Central America Using 1‐D Full‐Waveform Inversion

Abstract: Because the Earth's mantle is not perfectly elastic, seismic waves are slightly attenuated as they travel through it. Attenuation is mostly sensitive to temperature, with larger temperature leading to stronger attenuation, and can be measured from the analysis of seismic waveforms. More specifically, attenuation is parameterized with the quality factor, Q, which is inversely proportional to the attenuation, that is, lower Q indicates stronger attenuation. Together with the velocity of seismic shear waves (V S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 41 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…Because it is based on the fact that seismic velocity is affected by lateral changes in the depth of the phase transition from bridgmanite to post-perovskite (pPv), and therefore by lateral changes in the amount of pPv at a given location, the pdfs of T ref deduced from our approach depend on the transition temperature from bridgmanite to pPv close to the CMB, T pPv . Applying our method to measurements of V S and Q S beneath Central America (Borgeaud and Deschamps, 2021) and the Northern Pacific (Deschamps et al, 2019), we found that for T pPv = 3500 K the CMB temperature should be in the range 3,470-3880 K with a 95% likelihood. Because in our approach the value of T CMB depends on the value of T pPv right above the CMB, which remains poorly known, comparison between our results and available estimates is not straightforward.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 4 more Smart Citations
“…Because it is based on the fact that seismic velocity is affected by lateral changes in the depth of the phase transition from bridgmanite to post-perovskite (pPv), and therefore by lateral changes in the amount of pPv at a given location, the pdfs of T ref deduced from our approach depend on the transition temperature from bridgmanite to pPv close to the CMB, T pPv . Applying our method to measurements of V S and Q S beneath Central America (Borgeaud and Deschamps, 2021) and the Northern Pacific (Deschamps et al, 2019), we found that for T pPv = 3500 K the CMB temperature should be in the range 3,470-3880 K with a 95% likelihood. Because in our approach the value of T CMB depends on the value of T pPv right above the CMB, which remains poorly known, comparison between our results and available estimates is not straightforward.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Another constraint on local and horizontally averaged temperatures may be obtained from seismic attenuation, which is a thermally activated process (Minster and Anderson, 1981;Anderson and Given, 1982), implying that its amplitude depends on temperature. In the reminder of this paper, we detail this method, and we perform a preliminary application using models of V S and Q S obtained beneath Central America (Borgeaud and Deschamps, 2021) and the Northern Pacific (Deschamps et al, 2019).…”
Section: Open Access Edited Bymentioning
confidence: 99%
See 3 more Smart Citations